The microcirculation and its measurement in sepsis. (August 2017) - Charlton, Matthew; Sims, Mark; Coats, Tim; Thompson, Jonathan P
The microcirculation describes the smallest elements of the cardiovascular conducting system and is pivotal in the maintenance of homeostasis. Microcirculatory dysfunction is present early in the pathophysiology of sepsis, with the extent of microcirculatory derangement relating to disease severity and prognosis in ICU patients. However, at present microcirculatory function is not routinely monitored at the bedside. This article describes the pathophysiology of microcirculatory derangements in sepsis, methods of its measurement and evidence to support their clinical use.